The Digital Herbarium: Solutions for Data Collection and Identification of Indonesian Plant Diversity - Endro Setiawan; Dedy Darnaedi; Ismail Rachman; Teguh Triono; Campbell O. Webb (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Indonesia is one of the world’s biodiversity hotspots. It is estimated to be the home of 9.5% flowering plant species, making it the seventh country with the highest biodiversity. Plant data collection is necessary to ascertain the level of plant biodiversity, as such data help in conservation efforts and long-term management. One of the methods applied is the collection of plants, with the purpose to acquire as much data about its biological resources. The collected specimen are then gathered and processed into a herbarium to be used as an information source in managing biological resources. Unfortunately, there are some difficulties related to the making and management of a herbarium. This study aims to assess the advantages and disadvantages of photo-specimens (digital herbarium) for documenting plant biodiversity in Indonesia. The methods need steps including biological recording, specimen preparing, macro-mode capturing, and last stage identification. About 2149 plants have been gathered from Borneo, Seram, Waigeo, Flores and Sulawesi which consisted of 152 family, 512 genus, and 1,832 species, with a total of 30391 pictures of plant parts. From the experiment conducted on 672 specimens, it achieved 98.8 % accuracy on the family level and 80.1 % accuracy on the genus level, while the species level reached 78.8%. The results showed that digital herbarium can be used to conduct identification and data collection of plant biodiversity. Furthermore, this method is simple, cheap and relatively easier to conduct. The output is a catalog of plant species in specific areas, which provides better understanding about plant identification and biodiversity, enhances conservation practices, and provides better long-term protection for Indonesian plant biodiversity.